Clothes Don’t Make the Man (or Woman), but Gender Identity Might - Levi, Jennifer L. (Columbia Journal of Gender and Law, 2006)
The Ninth Circuit’s recent decision in Jespersen v. Harrah’s Operating Co., Inc.’ reflects the blinders on many contemporary courts regarding the impact of sex-differentiated dress requirements on female employees. Although some courts have acknowledged the impermissibility of imposing sexually exploitive dress requirements,3 they have done so only at the extreme outer limits, ignoring the concrete harms experienced by women (and men) who are forced to conform to externally imposed gender norms. On the other hand, some transgender litigants have recently succeeded in challenging sex-differentiated dress requirements. This success is due in part to their incorporation of disability claims based on the health condition associated with each litigant’s transgender identity. Such an approach has allowed transgender litigants to introduce evidence of the essentialism of gender identity and its inelasticity for a specific individual. In combining disability claims with sex discrimination claims, transgender litigants have advanced a broader agenda of challenging normative beliefs about gender for all persons, transgender and non-transgender alike.